2006
DOI: 10.1111/j.1348-0421.2006.tb03848.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural Requirements of Cholesterol for Binding to Vibrio cholerae Hemolysin

Abstract: Vibrio cholerae is the causative agent of cholera, which is characterized by severe secretory diarrhea in humans. The profuse secretory diarrhea that is characteristic of cholera is caused by a toxin produced by toxigenic V. cholerae when it colonizes the small intestine. Almost all V. cholerae, except the classical type, also produce a Vibrio cholerae hemolysin (VCH) monomer (8,13,23). It has been reported that a specific VCH with an apparent molecular mass of 65 kDa has strong cytotoxic effects (9,14,16,22,2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…In summary, the Ala425Val mutation severely affected the cholesterol-dependent mechanism of membrane interaction in the VCC protein, an alteration that also abolished formation of the functional pore by the membrane-bound toxin molecules. Earlier studies suggested that the presence of cholesterol in the membranes was a critical factor in optimal membrane binding, oligomerization, membrane insertion and pore formation by the VCC toxin [24][25][26][27][28][29]. Moreover, an optimal membrane pore-forming property of VCC was found to be tightly linked with its efficient interaction with the membrane [24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In summary, the Ala425Val mutation severely affected the cholesterol-dependent mechanism of membrane interaction in the VCC protein, an alteration that also abolished formation of the functional pore by the membrane-bound toxin molecules. Earlier studies suggested that the presence of cholesterol in the membranes was a critical factor in optimal membrane binding, oligomerization, membrane insertion and pore formation by the VCC toxin [24][25][26][27][28][29]. Moreover, an optimal membrane pore-forming property of VCC was found to be tightly linked with its efficient interaction with the membrane [24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies suggested that the presence of cholesterol in the membranes was a critical factor in optimal membrane binding, oligomerization, membrane insertion and pore formation by the VCC toxin [24][25][26][27][28][29]. Moreover, an optimal membrane pore-forming property of VCC was found to be tightly linked with its efficient interaction with the membrane [24][25][26][27][28][29]. Consistent with this, and based on the data presented here, we hypothesize that the Ala425Val mutation in the VCC toxin compromised its optimal cholesteroldependent membrane interaction mechanism that, in turn, abrogated crucial mechanism(s) triggering the conformational fine-tuning in the VCC molecular structure, required for the generation of functional transmembrane pore assembly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, membrane lipid components like cholesterol have been widely implicated in regulating the membrane pore formation process (25,26). In the case of VCC, the presence of cholesterol in the membrane lipid bilayer has been shown to be an obligatory requirement for efficient membrane oligomerization and functional membrane pore formation by the toxin (27)(28)(29)(30)(31)(32)(33). Cholesterol appears to regulate the mode of action of VCC by physically interacting with the toxin molecule and not by simply altering the physicochemical environment of the target membrane (32).…”
Section: Vibrio Cholerae Cytolysin (Vcc)mentioning
confidence: 99%
“…In the case of VCC, the presence of cholesterol in the membrane lipid bilayer has been shown to be an obligatory requirement for efficient membrane oligomerization and functional membrane pore formation by the toxin (27)(28)(29)(30)(31)(32)(33). Cholesterol appears to regulate the mode of action of VCC by physically interacting with the toxin molecule and not by simply altering the physicochemical environment of the target membrane (32). It is important to note here that the VCC toxin molecule itself has been examined only to a limited extent, in the context of exploring its oligomerization mechanism.…”
Section: Vibrio Cholerae Cytolysin (Vcc)mentioning
confidence: 99%